RBM10 inhibits cell proliferation of lung adenocarcinoma via RAP1/AKT/CREB signalling pathway - Jin, Xin (J Cell Mol Med, 2019)
Initial functional studies have demonstrated that RNA‐binding motif protein 10 (RBM10) can promote apoptosis and suppress cell proliferation; however, the results of several studies suggest a tumour‐promoting role for RBM10. Herein, we assessed the involvement of RBM10 in lung adenocarcinoma cell proliferation and explored the potential molecular mechanism. We found that, both in vitro and in vivo, RBM10 overexpression suppresses lung adenocarcinoma cell proliferation, while its knockdown enhances cell proliferation. Using complementary DNA microarray analysis, we previously found that RBM10 overexpression induces significant down‐regulation of RAP1A expression. In this study, we have confirmed that RBM10 decreases the activation of RAP1 and found that EPAC stimulation and inhibition can abolish the effects of RBM10 knockdown and overexpression, respectively, and regulate cell growth. This effect of RBM10 on proliferation was independent of the MAPK/ERK and P38/MAPK signalling pathways. We found that RBM10 reduces the phosphorylation of CREB via the AKT signalling pathway, suggesting that RBM10 exhibits its effect on lung adenocarcinoma cell proliferation via the RAP1/AKT/CREB signalling pathway.